Challenges to global security: geopolitics and power in an age of transition geopolitics and power in an age of transition - Solomon, Hussein; Solomon, Hussein; Toda Institute for Global Peace and Policy Research (London ; New York : I.B. Tauris : In association with the Toda Institute for Global Peace and Policy Research, 2008)
Ours is an age of great upheaval where change sometimes appears to be the only constant. Three of the most important forces driving such change are globalization, regionalization and democratization. This work makes an attempt to understand these forces, and to show how they impact on the vitally important question of global security.
The competition for power and legitimacy in an age of transition / Joseph A. Camilleri -- US nuclear policies / Michael D. Intriligator -- Regional security in Latin America / Benedicte Bull -- Regional security in South Asia / B.M. Jain -- Regional security in Southeast Asia / Joseph Y.S. Cheng -- Regional security in the European Union / Hripsime Nalbandyan -- Regional security in Russia and the near abroad / Olga A. Vorkunova -- Regional security in the Middle East / Mohammad El-Sayed Selim -- Africa's shaky security architecture : perspectives from SADC and the AU / Hussein Solomon -- Prospects for an Asian union / Beni Prasad Agarwal -- On the road to global security? / Hussein Solomon.
Includes bibliographical references and index.
Keywords: Security, International; Geopolitics; International relations; Geopolitics; International relations; Security, International